1999
DOI: 10.1086/307535
|View full text |Cite
|
Sign up to set email alerts
|

Obscuration of the Parsec‐Scale Jets in the Compact Symmetric Object 1946+708

Abstract: We present results of VLA and VLBA observations of the 1.420 GHz neutral hydrogen absorption associated with the Compact Symmetric Object 1946+708 (z=0.101). We find significant structure in the gas on parsec scales. The peak column density in the Hi (N HI ≃2.2×10 23 cm −2 ( Ts 8000K ) ) occurs toward the center of activity of the source, as does the highest velocity dispersion (∆V FWHM ≃350 km s −1 ). In addition, we find that the continuum spectra of the various radio components associated with these jets st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 36 publications
10
97
0
Order By: Relevance
“…VLBI studies available in the literature can be inspected to verify if such a trend exists. The covering factor is close to c f = 1 in the compact source 1946+708 (Peck et al 1999), however one can also find examples for compact sources with lower covering factor of c f ∼ 0.2 in B2352+495 (Araya et al 2010) and in 4C 12.5 . In extended sources c f = 1 is estimated in the re-started source 3C 293 (Beswick et al 2004).…”
Section: H I and Radio Morphologymentioning
confidence: 72%
“…VLBI studies available in the literature can be inspected to verify if such a trend exists. The covering factor is close to c f = 1 in the compact source 1946+708 (Peck et al 1999), however one can also find examples for compact sources with lower covering factor of c f ∼ 0.2 in B2352+495 (Araya et al 2010) and in 4C 12.5 . In extended sources c f = 1 is estimated in the re-started source 3C 293 (Beswick et al 2004).…”
Section: H I and Radio Morphologymentioning
confidence: 72%
“…More sources are reported by Mack et al (2009). OH: Peck et al (1999), O'Dea et al (2005), Gupta et al (2006) observed, in total, a dozen objects without success. Their upper limits on OH column density are in the range 10 14 -10 15 cm −2 which is at least ten times less than in the galactic Giant Molecular Clouds and less than in other types of (few) radio galaxies.…”
Section: Moleculesmentioning
confidence: 95%
“…However, the location of the radio and Xray absorbers in the host galaxy of the radio source are still debated too. In the limited sample of compact sources with available high angular resolution HI absorption measurements, the HI is typically detected against one or both radio lobes (Araya et al 2010, and references therein; Morganti et al 2013), with estimated covering factors, C f , vari-⋆ Data from the Westerbork Synthesis Radio Telescope ⋆⋆ Corresponding author:e-mail: ostorero@ph.unito.it able from ∼0.2 to ∼1 (e.g., Peck et al 1999;Morganti et al 2004). The general consensus is that the HI absorber has an inhomogeneous or clumpy nature, although the actual distribution of the gas is not known.…”
Section: Introductionmentioning
confidence: 99%